2020
DOI: 10.1111/ele.13667
|View full text |Cite
|
Sign up to set email alerts
|

Forest responses to last‐millennium hydroclimate variability are governed by spatial variations in ecosystem sensitivity

Abstract: Forecasts of future forest change are governed by ecosystem sensitivity to climate change, but ecosystem model projections are under‐constrained by data at multidecadal and longer timescales. Here, we quantify ecosystem sensitivity to centennial‐scale hydroclimate variability, by comparing dendroclimatic and pollen‐inferred reconstructions of drought, forest composition and biomass for the last millennium with five ecosystem model simulations. In both observations and models, spatial patterns in ecosystem resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
(95 reference statements)
1
5
0
Order By: Relevance
“…This hinders our ability to evaluate forest responses to climate variability over longer temporal scales. However, an analysis using paleo reconstructions of climate and forest biomass and composition showed that processes consistent with what we found may have helped forests tolerate hydro-climate variability over the last millennium (Rollinson et al 2021).…”
Section: Discussionsupporting
confidence: 80%
“…This hinders our ability to evaluate forest responses to climate variability over longer temporal scales. However, an analysis using paleo reconstructions of climate and forest biomass and composition showed that processes consistent with what we found may have helped forests tolerate hydro-climate variability over the last millennium (Rollinson et al 2021).…”
Section: Discussionsupporting
confidence: 80%
“…Other conifers MIPs (e.g., Dietze et al, 2011;Huntzinger et al, 2013;Richardson et al, 2012;Schaefer et al, 2012;Stoy et al, 2013;Wei et al, 2014) but also evaluate the forest structure, which is the key target of forest management operations. Likewise, we go beyond comparison of models to tree-ring reconstruction data to evaluate growth (e.g., Klesse et al, 2018;Rollinson et al, 2017Rollinson et al, , 2021 Huber et al, 2020). Low accuracy of BA among all models may be explained by simulated mortality reducing stand density below the observed stem numbers (Figure S9).…”
Section: Other Broadleavesmentioning
confidence: 99%
“…The forest ecosystem is one of the main ecosystems of the earth, which plays an important role in maintaining the stability of the biosphere and improving the ecological environment [ 22 , 23 , 24 ]. Microorganisms, such as bacteria and fungi, are highly sensitive to environmental changes; thus, they are often used as biological indicator species to evaluate interference, natural succession, ecological restoration, and forestry environmental management in the forest ecosystem.…”
Section: Microbial Indicators In Natural Ecosystemsmentioning
confidence: 99%